Marital status as the mediator role towards work engagement on life satisfaction among working women in Sabah, Malaysia - Elpidia Juli; Md Sayed Uddin; Trixie Marjorie Tangit (Penerbit UiTM, 2024)
Background: Work engagement is a good practice in work organizations and very important in this world today. In addition, work engagement has been implemented in many studies for two decades. Women populations are higher than men and they are highly needed to get involved in labor force to improve the stability of economy. However, in Malaysia, DOSM (Department of Statistics, Malaysia) produced statistics on where women that involved in labor force still lower than men. In addition, very few studies focused on work engagement among working-class women towards their life satisfaction in Sabah, Malaysia. Objective: This research aims to test marital status as the mediator role towards relationship between work engagement and life satisfaction among working-class women in Kota Kinabalu, Sabah, Malaysia. Methodology: A total of 348 working women in public sectors in Kota Kinabalu, Sabah, Malaysia participated in the study by using snowball sampling method. An online questionnaire and physical questionnaires distributed to the respondents at government sectors. Result: Working-class women’s marital status fully mediates the relationship between work engagement and Positive and Negative Affect Schedule (PANAS), which is one of dimensions in life satisfaction. Further research is needed to investigate specific marital status that has higher level of mediator role towards the relationship between work engagement and life satisfaction among working-class women in Sabah, Malaysia.